2014
DOI: 10.2147/cia.s60146
|View full text |Cite
|
Sign up to set email alerts
|

Progressive dysphagia and neck pain due to diffuse idiopathic skeletal hyperostosis of the cervical spine: a case report and literature review

Abstract: Diffuse idiopathic skeletal hyperostosis (DISH) is considered an underdiagnosed and mostly asymptomatic nonprimary osteoarthritis. The etiology of DISH remains unknown and the validated diagnostic criteria are absent. This condition is still recognized radiologically only. Rarely, large projecting anterior osteophytes result in esophageal impingement and distortion leading to dysphagia. We report the case of progressive dysphagia and neck pain due to DISH of the cervical spine in a 70-year-old man, which was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 11 publications
0
15
0
1
Order By: Relevance
“…However, previous reports did not address the extent of the osteophyte resection in detail 16,18) . Some surgeons prefer the complete resection of all cervical spine osteophytes [19][20][21] . However, it was also reported that dysphagia persisted unchanged following surgery with extensive C3-6 osteophyte resection 20) .…”
Section: Discussionmentioning
confidence: 99%
“…However, previous reports did not address the extent of the osteophyte resection in detail 16,18) . Some surgeons prefer the complete resection of all cervical spine osteophytes [19][20][21] . However, it was also reported that dysphagia persisted unchanged following surgery with extensive C3-6 osteophyte resection 20) .…”
Section: Discussionmentioning
confidence: 99%
“…OALL is generally considered as a part of DISH and is classified into three types on the radiological basis 4. Segmental type is defined as partial or total ossification over a vertebral body without involving the disc space.…”
Section: Discussionmentioning
confidence: 99%
“…There is no conclusive correlation between symptoms and the size of the osteophytes: however, advanced age has been correlated with the severity of symptoms. This leads to various reports finding the strongest correlation with DISH being sex and age [1,2,5,6]. …”
mentioning
confidence: 97%
“…It is commonly progressive in nature and acute presentation is very unusual. There are several theories to explain dysphagia [2,[5][6][7]: a) Growth where the esophagus is anatomically anchored. b) Physical obstruction of the esophageal lumen by extrinsic compression.…”
mentioning
confidence: 99%
See 1 more Smart Citation